Analisis Hukum Terhadap Badan Usaha Kecil Menengah Makanan Yang Tidak Mendaftarkan Produknya Ke Bpom Dan Lebel Halal Ditinjau Dari Undang – Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen (Studi Pada Majelis Ulama Kota Medan) - Ervina Sari Sipahutar (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
Abstract  This study aims to determine the rules of inclusion of Halal (legal based on Islamic law) and BPOM (Agency for drugs and food control) labels on food products of small and medium enterprises. The importance of the study is to ensure legal protection of consumer’s rights violated by business actors in consuming food without Halal label based on Law No.8 of 1999 on Consumer Protection. The result of this analysis shows the factors why the small and medium food companies do not include Halal and BPOM labels on the packaging of their food products. It can be seen from the presence of un-standardized food products without Halal label. This shows the lack of supervision of food products by the apparatus. Consequently, consumer protection is needed based on Law no. 8 of 1999 which states that the right of consumers is the right to get comfort and safety in consuming goods or services. This Act shows that every consumer, including Muslim consumers, is entitled to obtain goods and services that are comfortable and not contrary to their religious principles, that is Halal. Keywords: State-owned enterprises, food products, BPOM, Halal Label